Monetary policy and stock market volatility - Dirk Bleich; Ralf Fendel; Jan-Christoph Rülke (Deutsche Bundesbank, 2013)
We estimate forward-looking interest rate reaction functions in the spirit of Taylor (1993) for four major central banks augmented by implicit volatilities of stock market indices to proxy financial market stress. Our results suggest that the Bank of England, the Federal Reserve Bank and the European Central Bank systematically respond to an increase of the implicit volatility by a decrease in the interest rate. We take our results as strong evidence that central banks use interest rates to stabilize financial markets in periods of financial market stress.
Keywords: E43; E58; G12; 330; Monetary policy; Taylor rule; Asset prices